2021
DOI: 10.3390/ijms22179503
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial Hemichannels and Pannexons: The Hidden Link between Maternal Inflammation and Neurological Disorders

Abstract: Maternal inflammation during pregnancy causes later-in-life alterations of the offspring’s brain structure and function. These abnormalities increase the risk of developing several psychiatric and neurological disorders, including schizophrenia, intellectual disability, bipolar disorder, autism spectrum disorder, microcephaly, and cerebral palsy. Here, we discuss how astrocytes might contribute to postnatal brain dysfunction following maternal inflammation, focusing on the signaling mediated by two families of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 228 publications
(356 reference statements)
0
5
0
Order By: Relevance
“…It has been demonstrated that pannexin1 and connexin43 form unopposed functional hemichannels in astrocytes [38][39][40][41][42]. Astroglial gliotransmitter release through connexin43-hemichannels was enhanced by decreasing the extracellular Ca 2+ level, whereas that through pannexin1-hemichannels was probably independent of the extracellular Ca 2+ level [23,27,28].…”
Section: Effects Of Extracellular Ca 2+ Removal On Astroglial Hfo-evo...mentioning
confidence: 99%
“…It has been demonstrated that pannexin1 and connexin43 form unopposed functional hemichannels in astrocytes [38][39][40][41][42]. Astroglial gliotransmitter release through connexin43-hemichannels was enhanced by decreasing the extracellular Ca 2+ level, whereas that through pannexin1-hemichannels was probably independent of the extracellular Ca 2+ level [23,27,28].…”
Section: Effects Of Extracellular Ca 2+ Removal On Astroglial Hfo-evo...mentioning
confidence: 99%
“…On the other hand, NO mediated S-nitrosylation of Px1 channels inhibits opening [ 140 ]. Therefore, these channels have been suggested to open via a different mechanism, as described in detail below [ 141 ].…”
Section: Effect Of Inflammation In the Absence Of Hi On Gap Junctions...mentioning
confidence: 99%
“…Finally, after injury, increased levels of inflammatory mediators and different cytokines avoid synaptic regeneration and exacerbate hypoxia and ischemia 6 . The formation of scars serves as a physical and chemical barrier, inhibiting synapses' extension and growth as well as nerve regeneration 7,8 . Indeed, numerous physiological processes, such as the availability of neurotrophic factors, axon regeneration, synaptic plasticity, and the microenvironment, contribute to the repair and regeneration of the central nervous system (CNS) following injuries, and the corresponding mechanisms are extremely complex 9 …”
Section: Introductionmentioning
confidence: 99%
“…6 The formation of scars serves as a physical and chemical barrier, inhibiting synapses' extension and growth as well as nerve regeneration. 7,8 Indeed, numerous physiological processes, such as the availability of neurotrophic factors, axon regeneration, synaptic plasticity, and the microenvironment, contribute to the repair and regeneration of the central nervous system (CNS) following injuries, and the corresponding mechanisms are extremely complex. 9 Throughout development, the brain and spinal cord are established from a small number of neural stem cells (NSCs) lining the neural tube.…”
mentioning
confidence: 99%